2021
DOI: 10.4067/s0716-10182021000100081
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenemasas en aislamientos de Pseudomonas aeruginosa resistentes a carbapenémicos aisladas en hospitales de Chile

Abstract: Introducción: La resistencia a carbapenémicos mediada por carbapenemasas en Pseudomonas aeruginosa es un mecanismo importante; sin embargo, la pérdida de la porina OprD continúa siendo el mecanismo más frecuente. Objetivo: Determinar la proporción de aislados de P. aeruginosa, resistentes a imipenem y/o meropenem, productores de carbapenemasas, el tipo de enzima producida y la relación genética entre los aislados. Material y Métodos: Se incluyó 113 aislados resistentes al menos a un carbapenémico, provenientes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The 53 studies included in this review were conducted in American, European, and Asian countries. China (14 studies) [ 14 , 15 , 17 , 19 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], Brazil (10 studies) [ 21 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], and Colombia (9 studies) [ 22 , 26 , 27 , 28 , 29 , 51 , 52 , 53 , 54 ] were the countries with the most reported studies, followed by Puerto Rico (4 studies) [ 55 , 56 , 57 , 58 ], Chile (2 studies) [ 59 , 60 ], Argentina (2 studies) [ 61 , 62 ], Vietnam (1 study) [ 63 ], Trinidad and Tobago (1 study) [ 64 ], Nepal (1 study) [ 65 ], India (1 study) [ 66 ], Germany (1 study) [ 18 ], Spain (1 study) [ 6 ], and the USA (1 study) […”
Section: Resultsmentioning
confidence: 99%
“…The 53 studies included in this review were conducted in American, European, and Asian countries. China (14 studies) [ 14 , 15 , 17 , 19 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], Brazil (10 studies) [ 21 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], and Colombia (9 studies) [ 22 , 26 , 27 , 28 , 29 , 51 , 52 , 53 , 54 ] were the countries with the most reported studies, followed by Puerto Rico (4 studies) [ 55 , 56 , 57 , 58 ], Chile (2 studies) [ 59 , 60 ], Argentina (2 studies) [ 61 , 62 ], Vietnam (1 study) [ 63 ], Trinidad and Tobago (1 study) [ 64 ], Nepal (1 study) [ 65 ], India (1 study) [ 66 ], Germany (1 study) [ 18 ], Spain (1 study) [ 6 ], and the USA (1 study) […”
Section: Resultsmentioning
confidence: 99%
“…Giacoboni et al, and Yauri‐Condor et al, in Peru, reported similar results with CAS for Enterobacterales 19,20 . The use of this test has been extended to P. aeruginosa and Acinetobacter baumannii to identify plasmid‐mediated resistance to colistin using CAS with EDTA 21,22 …”
Section: Discussionmentioning
confidence: 76%
“…19,20 The use of this test has been extended to P. aeruginosa and Acinetobacter baumannii to identify plasmid-mediated resistance to colistin using CAS with EDTA. 21,22 Five isolates of K. pneumoniae with MIC 4 μg/ml gave negative results in CA-3 (2.97% mE), which could be explained due a large number of isolates with MIC 4 μg/ml (n = 45) was included, and this type of errors are frequently reported to occurred near the breakpoint. Errors in MIC values of 2 μg/ml were not observed, but only 17 isolates were included.…”
Section: Discussionmentioning
confidence: 99%